2010
DOI: 10.1002/acr.20003
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of nonspecific and radiating low back pain: followup of 24–39‐year‐old adults of the Young Finns Study

Abstract: Objective. The full panorama of the types and severity of low back pain during the life course is poorly known. We studied the incidence and severity of nonspecific and radiating low back pain based on a recent followup on a representative sample of the Finnish general population. Methods. As part of the ongoing Young Finns Study, participants ages 24 -39 years who were free from low back pain at baseline in 2001 were included (n ‫؍‬ 1,224). We estimated the incidence of nonspecific and radiating low back pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…The prevalence rate of NLBP in our study was 13.1%, which is consistent with the findings of 10.0–49.0% in literature according to the definition of NLBP [5, 1113, 36]. The validated pre-scoring system we developed based on ten factors had a high discriminative power at the bootstrap-corrected AUC of 0.861 and was strongly supported by the external validation (AUC of 0.821).…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence rate of NLBP in our study was 13.1%, which is consistent with the findings of 10.0–49.0% in literature according to the definition of NLBP [5, 1113, 36]. The validated pre-scoring system we developed based on ten factors had a high discriminative power at the bootstrap-corrected AUC of 0.861 and was strongly supported by the external validation (AUC of 0.821).…”
Section: Discussionsupporting
confidence: 91%
“…Participants were classified as having radiating LBP (pain that radiates below the knee) or non-specific LBP if they reported that their pain had lasted 7 days or more during the previous 12 months. Similar procedures have been applied also previously (Shiri et al, 2010b(Shiri et al, , 2013).…”
Section: Low Back Painmentioning
confidence: 91%
“…It is a common symptom – reported prevalence rates ranging from 1% to 43% (Konstantinou and Dunn, 2008) – and may be accompanied by clinical findings suggestive of a herniated disc or nerve root irritation (Ropper and Zafonte, 2015) in “clinically verified sciatica”. In two Finnish cohort studies, the prevalence of lumbar radicular pain lasting longer than seven days during the past 12 months among participants who had previously been free from the symptom was 9% and 12% (Miranda et al, 2002; Shiri et al, 2010c), and that of lumbar radicular pain lasting longer than 30 days 3.0% and 3.4% (Miranda et al, 2002; Shiri et al, 2010c). The risk of lumbar radicular pain increased with age and did not differ between men and women (Miranda et al, 2002; Shiri et al, 2010c).…”
Section: Introductionmentioning
confidence: 99%